PENGARUH KONEKSI POLITIK, PERSISTENSI LABA, DAN KEKUATAN LABA TERHADAP NILAI PERUSAHAAN - Angelia, Angelia; Munandar, Agus (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The aim of this research is to prove that there is an influence between political connections, earnings persistence, and earnings power on company value. The sample was selected based on the purposive sampling method and includes 33 companies listed on the Indonesian Stock Exchange. The observation period is 2020 to 2022. Multiple regression analysis is used to test the hypothesis, and the results show that political connections have no effect on company value, while earnings persistence and earnings strength have an effect on company value. This implies that a firm's financial performance and stability, as reflected in persistent and robust earnings, have a more substantial influence on its overall value than any potential political affiliations. This insight is valuable for stakeholders and financial analysts, emphasizing the critical role of financial metrics over political connections in assessing and understanding a company's value.